Green Synthesis of TiO2 Nanoparticle Using Cinnamon Powder Extract and the Study of Optical Properties - Nabi, Ghulam; Raza, Waseem; Tahir, M. B. (Journal of inorganic and organometallic polymers and materials, 2020)
The pure TiO 2 nanoparticles have been synthesized by a simplistic eco-friendly green method using extract of cinnamon powder for the first time. The cinnamic acid present in the cinnamon works as the capping agent during the reaction. TiO 2 nanoparticles were characterized by using X-ray diffraction (XRD) which conformed the anatase phase TiO 2 with average crystallite size 70.1 nm. Scanning electron microscopy (SEM) micrographs suggests that the particles exhibit spherical shapes and uniformly distributed over the surface with size range 70–150 nm. The energy dispersive X-ray spectroscopy (EDX) shows the presence of oxygen and titanium peaks which confirmed the formation of TiO 2 pure nanoparticles. From the UV–Vis spectroscopic studies the band gap comes out to be 3.2 eV which confirmed the formation of TiO 2 nanoparticles. The optical properties have also been studied by PL that indicates the formation of oxygen vacancies and self-trapped excitons in the material. The samples showed the enhanced photocatalytic property.